1865 Fla. Laws 23, 25-27. - (:unkn) unknown (My University, 1866)
An Act Prescribing Additional Penalties for the Commission of Offences against the State, and for Other Purposes, Ch. 1460, No. 3, § 12: That it shall not be lawful for any negro, mulatto, or other person of color, to own, use or keep in his possession or under his control, any Bowie-knife, dirk, sword, fire-arms or ammunition of any kind, unless he first obtain a license to do so from the Judge of Probate of the county in which he may be a resident for the time being
Keywords: ENSLAVED PERSONS & OTHER MINORITIES